2008
DOI: 10.1038/nature07542
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour jets inside the plume of gas leaving Enceladus

Abstract: A plume of water vapour escapes from fissures crossing the south polar region of the Saturnian moon Enceladus. Tidal deformation of a thin surface crust above an internal ocean could result in tensile and compressive stresses that would affect the width of the fissures; therefore, the quantity of water vapour released at different locations in Enceladus' eccentric orbit is a crucial measurement of tidal control of venting. Here we report observations of an occultation of a star by the plume on 24 October 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 17 publications
15
99
1
Order By: Relevance
“…Many of the moons of the outer planets and Pluto contain a significant fraction of water, with Tethys possibly consisting almost entirely of water ice (Thomas et al 2007). Some, such as Jupiter's Europa and Saturn's Enceladus, are thought to contain a tidally heated global or local subsurface ocean of liquid water beneath the outer shell of ice (Carr et al 1998;Manga and Wang 2007;Nimmo et al 2007;Hansen et al 2008). …”
Section: Water In the Planetsmentioning
confidence: 99%
“…Many of the moons of the outer planets and Pluto contain a significant fraction of water, with Tethys possibly consisting almost entirely of water ice (Thomas et al 2007). Some, such as Jupiter's Europa and Saturn's Enceladus, are thought to contain a tidally heated global or local subsurface ocean of liquid water beneath the outer shell of ice (Carr et al 1998;Manga and Wang 2007;Nimmo et al 2007;Hansen et al 2008). …”
Section: Water In the Planetsmentioning
confidence: 99%
“…Water emitted from Enceladus' plumes in jets with 1 km s −1 velocity (Hansen et al 2008(Hansen et al , 2011 initially forms a narrow torus. However, the observed OH distribution (Melin et al 2009) requires acceleration and spreading, for which processes identified early on (Jurac & Richardson 2005;Johnson et al 2006) include the release of kinetic energy under photodissociation and collisions with rapid torus ions.…”
Section: Excitation and Torus Modelsmentioning
confidence: 99%
“…The black line shows the averaged spectrum with a peak antenna temperature of 32 mK and an SNR at the level of 7.0σ. the detection by Hansen et al (2006Hansen et al ( , 2008 of Enceladus' water vapour in UV-absorption. We note that over the preceding 14 months the Medicina telescope did not detect a line exceeding 3σ from Enceladus.…”
Section: Resultsmentioning
confidence: 99%